(untitled) (Equilibrium: Jurnal Pendidikan, 2026)
This research is motivated by the importance of the role of Islamic Religious Counselors as agents of change in community empowerment, which until now has tended to be understood normatively and has not been studied in depth from a social perspective. This study aims to analyze the role of Islamic Religious Counselors in community empowerment in Enrekang Regency. Theoretically, this research benefits from enriching sociological studies, while practically, it serves as evaluation material for policy makers. This research uses a descriptive qualitative approach with a case study design conducted at the Ministry of Religious Affairs Office in Enrekang Regency for three months. The main instrument is the researcher with the support of interview guidelines, observation, and documentation. Data were collected through in-depth interviews, participatory observation, and documentation using primary and secondary data sources. Data analysis uses the Miles and Huberman model, while data validity is tested through triangulation and member checking. The results show that Islamic Religious Counselors play a role as facilitators, mediators, and motivators in community empowerment through a participatory and contextual approach. The implications of this research emphasize the importance of strengthening the capacity of counselors and institutional support to increase the effectiveness of their role in encouraging sustainable social change.